Examining The Drivers Of Decision-Making: A Methodical Approach For Choices Of Construction Project Delivery Methods (Journal of Namibian Studies : History Politics Culture, 2024)
Different approaches exist for obtaining construction projects, including options like design-build (DB), design-bid-build (DBB), construction management at risk (CM-at-risk), and integrated project delivery (IPD), among several alternatives. Selecting the most suitable procurement plan for a specific project requires careful consideration of each approach. In this process, a selection approach and criteria need to be evaluated. This study aims to enhance clarity by synthesizing existing literature on factors influencing project delivery selection and presenting a comprehensive list of these factors. A methodical analysis was conducted, initially identifying many papers, which were narrowed down to 57 relevant to construction projects. Through the examination and consolidation of recurring themes, a definitive list of 11 criteria and 22 sub-criteria was established. The most frequently reported factors, in descending order, included concerns of owner, contractor, cost, time, quality, risks, contracts and claims, laws and regulations, complexity, size, and type. It's important to note that these factors vary from project to project, and the study provides an argument on how they influence the project delivery methods (PDMs) selection. The results of this research provide valuable insights into the impacts associated with different PDMs in the construction industry. This study informs industry professionals, policymakers, and project owners about the implications of their choices.